Nutritional status of pre-school children – A cross-sectional study in Mingora, Swat - Afridi, Muhammad Faisal; Khushdil, Arshad; Riaz, Sara; Ehsan, Azra (Journal of Postgraduate Medical Institute, 2014)
Objective: The main aim of the study was to assess the nutritional status of pre-school children in Mingora city of Swat. Methodology: A community based, cross-sectional study was conducted in Mingora city - an urban area of Swat valley, from April to December 2013, to determine the current nutritional status of pre-school children (2-5years age group). A total of 550 children were selected by convenience sampling method. Anthropometric data was collected about height and weight. It was compared against National Center for Health Statistics (NCHS) standards. It was analysed using SPSS version 16 and Microsoft Excel 2010. Results: Out of total of 550 children, 46% (n=253) were males while 54% (297) were females. Mean weights of the children ranged from 11.6 to 19.3 kg (±1.9kg) and mean heights of different age groups ranged from 85.7 to 111.6 cm (±3.99 cm). Height for age parameter shows that 88% (n=484) of children are within normal range. Weight for Age parameter shows that 82% (n=451) of children had normal weight for age; 14% (n=77) were underweight; 8% (n=44) of the children were wasted; while 8% (n=44) were stunted. Conclusion: The prevalence of childhood malnutrition was very low in the geographic area studied. Similar studies in other geographic areas are indicated to establish a complete regional nutritional profile.